Occupational exposure to respirable crystalline silica and risk of autoimmune rheumatic diseases: a nationwide cohort study. (18th January 2021) - Boudigaard, Signe Hjuler; Schlünssen, Vivi; Vestergaard, Jesper Medom; Søndergaard, Klaus; Torén, Kjell; Peters, Susan; Kromhout, Hans; Kolstad, Henrik A
Abstract: Background: Exposure to respirable crystalline silica is suggested to increase the risk of autoimmune rheumatic diseases. We examined the association between respirable crystalline silica exposure and systemic sclerosis, rheumatoid arthritis, systemic lupus erythematosus and small vessel vasculitis. Methods: In a cohort study of the total Danish working population, we included 1 541 505 male and 1 470 769 female workers followed since entering the labour market 1979–2015. Each worker was annually assigned a level of respirable crystalline silica exposure estimated with a quantitative job exposure matrix. We identified cases of autoimmune rheumatic diseases in a national patient register and examined sex-specific exposure-response relations by cumulative exposure and other exposure metrics. Results: We identified 4673 male and 12 268 female cases. Adjusted for age and calendar year, men exposed to high levels of respirable crystalline silica compared with non-exposed showed increased incidence rate ratio (IRR) for the four diseases combined of 1.53 [95% confidence interval (CI): 1.39–1.69], for systemic sclerosis of 1.62 (1.08–2.44) and rheumatoid arthritis of 1.57 (1.41–1.75). The overall risk increased with increasing cumulative exposure attained since entering the workforce [IRR: 1.07 (1.05–1.09) per 50 µg/m 3 -years]. Female workers were less exposed to respirable crystalline silica, but showed comparable risk patterns with overall increased risk with increasing cumulative exposure [IRR: 1.04 (0.99–1.10) per 50 µg/m 3 -years]. Conclusions: This study shows an exposure-dependent association between occupational exposure to respirable crystalline silica and autoimmune rheumatic diseases and thus suggests causal effects, most evident for systemic sclerosis and rheumatoid arthritis.